Impaired kidney function among young healthcare workers with long working hours and night work - Wan-Chin Chen; Hsiao-Yu Yang (Scandinavian Journal of Work, Environment & Health, 2024)

(untitled)
OBJECTIVES: We aimed to evaluate the association between long working hours, night work, and estimated glomerular filtration rate (eGFR) among young healthcare workers. METHODS: We conducted a retrospective cohort study among healthcare workers in a tertiary medical center in Taiwan from 2002 to 2021. Other than physicians, all hospital employees aged 20–65 years with documented yearly working hours and an annual blood test including creatinine were eligible. We excluded participants with eGFR <60 ml/min/1.73 m^2 and proteinuria at enrollment to focus on early renal impairment. Total working hours, night working hours, and eGFR in each year were collected. We assessed the relationship of total working hours and night and non-night working hours with eGFR using the generalized linear mixed model, adjusting for demographic, comorbidities, and laboratory profiles. RESULTS: The study included 10 677 participants with a mean age of 27.2 (standard deviation 7.1) years. The mean follow-up duration was 6.2 years. For every 10-hour increase in total weekly working hours, the eGFR decreased by 0.86 [95% confidence interval (CI) 0.61–1.11] ml/min/1.73 m^2. For every 10-hour increase in weekly night working hours, the eGFR decreased by 0.25 (95% CI 0.07–0.42) ml/min/1.73 m^2. In stratified analysis, the negative associations between total working hours and eGFR remained in the subgroups of individuals aged <40 years and those without hypertension or diabetes, with a P-value for interaction of <0.05. CONCLUSIONS: Longer working hours and night work were associated with lower eGFR among healthcare workers.